(untitled) (Lumen Veritatis: Jurnal Filsafat dan Teologi, 2026)
This paper examines the metaphysical polemic in the tradition of Islamic philosophy through the debate between Al-Ghazali and Ibn Rushd concerning several central doctrines of the philosophers. The debate originates from Al-Ghazali’s theological critique of the metaphysical views of the Peripatetic philosophers, which were strongly influenced by the thought of Aristotle and Avicenna. In his work Tahafut al-Falasifah, Al-Ghazali presents a rigorous critique of three major metaphysical issues: the eternity of the world, God’s knowledge of particulars, and bodily resurrection in the afterlife. This critique was later addressed systematically by Ibn Rushd in his work Tahafut al-Tahafut, in which he seeks to defend the rational coherence of philosophy and to demonstrate that there is no fundamental contradiction between reason and revelation when both are properly understood. This research employs a qualitative approach, combining library research with a philosophical analysis of the arguments advanced by both thinkers. The findings indicate that the polemic between Al-Ghazali and Ibn Rushd is not merely a conflict between theology and philosophy, but rather an intellectual dialogue that enriches the development of metaphysical thought in the Islamic intellectual tradition. Al-Ghazali emphasizes the limits of philosophical rationality in comprehending transcendent reality, whereas Ibn Rushd affirms the legitimacy of reason as an essential means of interpreting truth. Ultimately, this debate illustrates the dynamic dialectic between revelation and reason within the Islamic intellectual tradition.